Analytical Investigation of Projectile Motion in Midair - Chudinov, Peter; Eltyshev, Vladimir; Barykin, Yuri (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Here is studied a classic problem of the motion of a projectile thrown at an angle to the horizon. The air drag force is taken into account as the quadratic resistance law. An analytic approach is used for the investigation. Equations of the projectile motion are solved analytically. All the basic functional dependencies of the problem are described by elementary functions. There is no need for to study the problem numerically. The found analytical solutions are highly accurate over a wide range of parameters. The motion of a baseball and a badminton shuttlecock are presented as examples.